Locomotor adaptation: Significance and underlying neural mechanisms - Tetsuya Ogawa; Noritaka Kawashima; Kimitaka Nakazawa (Japanese Society of Physical Fitness and Sports Medicine, 2015)
Human locomotion is flexible in meeting the requirements of given environmental or task demands. Hence, in everyday life, we can walk, run, and skip in environmental surroundings that vary from hour to hour and even from second to second. In making such flexible adjustments, a sense of "adaptability" attained by the central nervous system plays an important role. In the literature, adaptation studies focusing on locomotion have attracted a great deal of attention in recent years for their potential application to the designing of gait training programs, and as a useful method for revealing the specific mechanisms underlying human locomotion. In this review article, to address how locomotor adaptation is related to social locomotion, the authors introduce knowledge accumulated in recent decades, particularly that related to two different types of locomotor adaptation studies: first, studies that address the general features of locomotor adaptation including underlying neural mechanisms, and second, those that use experimental paradigms of locomotor adaptation to reveal the context-dependency of locomotion. It should be noted that, although knowledge of locomotor adaptation has been increasing, the field is still largely unexplored, and further intensive research in the future is necessary.